Massive cerebral fat embolism leading to brain death: A rare presentation - Aggarwal, Richa (Indian J Crit Care Med, 2015)
Fat embolism syndrome (FES) typically consists of a triad of neurological, pulmonary, and cutaneous symptoms. There exist few case reports of FES involving central nervous system (CNS) only without pulmonary involvement. In most of such cases, CNS involvement is partial, and patients recover fully neurologically within days. We report a rare and unusual case of massive cerebral fat embolism that led to brain death in trauma patient.